Promoting sustainable local economic development initiatives Case studies - Venter, Marius (Centre for Local Economic Development: Topics in Local Development, 2022)
This book endeavours to outline case studies that promote sustainable Local Economic Development (LED) initiatives. It is generally believed that local governments are the foot soldiers of LED. However, this seems to be a myth, as local governments in South Africa and elsewhere have not yet fulfilled this mandate and have been struggling for several years to implement LED initiatives. The distinctive merit of this book lies in the way it combines the South African context with the wider international development context in ways that there is a flow of information and ideas both ways. The book is an essential part of this sequence of ideas development and action at a critical time for strategic action directed at a sustainable future. It showcases case studies and responses to the impacts of globalisation as a bridge between urban/rural and institutional action and reveals avenues for local government leadership in communities, research, student engagement and wider interactions.